Pola Pencarian Informasi Generasi Z Melalui Media Sosial (studi kasus di kalangan penggemar Kakao Webtoon) - Nurjumiati, Nurjumiati; Primadesi, Yona (Departemen Informasi Perpustakaan dan Kearasipan, 2024)
This research aims to describe generation Z's information seeking patterns via social media among Kakao Webtoon fans. This research is qualitative research with a case study method. Determining informants in this research was carried out using a purposive sampling method. Data collection was carried out using interviews, observation and documentation methods. Validation of data was carried out by triangulating sources and analyzing through data reduction, data presentation and drawing conclusions. The results of this research show that in the initiation stage, generation Z feels the need for information due to encouragement or certain moments. In the selection stage, generation Z chooses social media and accounts that are considered relevant. Generation Z's exploration stage formulates the information they will seek and suits their needs, such as specific and interesting information. This information can be seen from the caption, official account, as well as seeing other people's responses to the post. In the collection stage, generation Z stores the information obtained using the bookmark, like, save and share links to save. The information that has been obtained is also shared via send DM, retweet, quote tweet, story and share link, which is found on social media. The presentation stage uses information for one's own benefit which is used for mutual discussion between fellow fans.